Intracranial Hemorrhage and Early Mortality in Patients Receiving Extracorporeal Membrane Oxygenation for Severe Respiratory Failure - Arachchillage, Deepa R.J.; Passariello, Maurizio; Laffan, Michael; Aw, TC; Owen, Leah; Banya, Winston; Trimlett, Richard; Morgan, Cliff; Patel, Brijesh V.; Pepper, John; Ledot, Stephane (Seminars in Thrombosis and Hemostasis, 2018)
Intracranial hemorrhage (ICH) is a serious complication in patients receiving veno-venous extracorporeal membrane oxygenation (VV-ECMO) and is associated with high mortality. It is unknown whether ICH may be a consequence of the ECMO or of an underlying disease. The authors first aimed to assess the incidence of ICH at initiation and during the course of VV-ECMO and its associated mortality. The second aim was to identify clinical and laboratory measures that could predict the development of ICH in severe respiratory failure. Data were collected from a total number of 165 patients receiving VV-ECMO from January, 2012 to December, 2016 in a single tertiary center and treated according to a single protocol. Only patients who had a brain computed tomography within 24 hours of initiation of ECMO (n = 149) were included for analysis. The prevalence and incidence of ICH at initiation and during the course of VV-ECMO (at median 9 days) were 10.7% (16/149) and 5.2% (7/133), respectively. Thrombocytopenia and reduced creatinine clearance (CrCL) were independently associated with increased risk of ICH on admission; odds ratio (95% confidence interval): 22.6 (2.6–99.5), and 10.8 (5.6–16.2). Only 30-day (not 180-day) mortality was significantly higher in patients with ICH on admission versus those without (37.5% [6/16] vs 16.4% [22/133]; p = 0.03 and 43.7% [7/16] vs 26.3% [35/133]; p = 0.15, respectively). Reduced CrCL and thrombocytopenia were associated with ICH at initiation of VV-ECMO. The higher incidence of ICH at initiation suggests it is more closely related to the severity of the underlying lung injury than to the VV-ECMO itself. ICH at VV-ECMO initiation was associated with early mortality.
Keywords: extracorporeal membrane oxygenation; respiratory failure; intracranial hemorrhage; cerebral ischemic infarction; venous thrombosis; anticoagulation